(untitled) (Journal of Applied Oral Science, 2021)
Objective: The microbial composition of pericoronitis (Pc) is still controversial; it is not yet clear if the microbial profile of these lesions is similar to the profile observed in periodontitis (Pd). Therefore, the aim of the present study was to describe the microbial profile of Pc lesions and compare it directly with that of subjects with Pd. Methodology: Subjects with Pc and Pd were selected, and subgingival biofilm samples were collected from (i) third molars with symptomatic Pc (Pc-T), (ii) contralateral third molars without Pc (Pc-C) and (iii) teeth with a probing depth >3 mm from subjects with Pd. Counts and proportions of 40 bacterial species were evaluated using a checkerboard DNA-DNA hybridization technique. Results: Twenty-six patients with Pc and 18 with Pd were included in the study. In general, higher levels of microorganisms were observed in Pd. Only Actinomyces oris and Eubacterium nodatum were present in higher mean counts in the Pc-T group in comparison with the Pc-C and Pd-C groups (p<0.05). The microbiota associated with Pc-T was similar to that found in Pc-C. Sites with Pc lesions had lower proportions of red complex in comparison with the Pd sites. Conclusion: The microbiota of Pc is very diverse, but these lesions harbour lower levels of periodontal pathogens than Pd.